Conquered conquerors: love and war in the song of songs - Verde, Danilo (Ancient Israel and its literature, 2020)
"Danilo Verde explores the Song of Songs' use of military language to describe both love and lovers from the perspective of cognitive metaphor theory. love is war is one of the main recurring themes of the Song, and the poem's representations of love/rs using military imagery thematically connects the poem, providing the reader with a coherent and conceptually unified understanding of the Song. Additionally, this book investigates how the Song conceptualizes the female and the male, revealing their tight interconnection in the poem. By exploring one of the Song's most overlooked images, Conquered Conquerors provides fresh insights into the Song's figurative language and the conceptualization of gender in biblical literature"--